Directive Speech Acts Represented as Teacher Feedback at Indonesian Higher Education Level - Sandy Wirawan; Nurul Chojimah; Eni Sugiharyanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study scrutinizes the common types of directive speech act performed by the teacher in the form of written feedback along with its function classification. Descriptive qualitative was used as the research design. For data collection, observation and documentation were used to obtain utterances performed by the speaker. In this regard, one English lecturer at one of universities in Indonesia was chosen teaching one class under the subject of Advanced Reading. Then, thematic analysis was used to analyze and categorize the data set. There were 81 number of data found from this study as directive speech act in the teacher feedback. This study revealed that direct acts were dominant with 50 data while the indirect acts consisted of 31 data. Furthermore, out of six (6) types of directive speech acts, the findings demonstrated that the function of requestives and questions were the most frequent acts performed by the teacher in the feedback. The result of this study suggested that the further research may take account into different criteria of giving feedback, such as the other types of speech acts, the teacher gender, and the subject of the class.